Prevalence of premarital sex, HIV/AIDS related knowledge, attitudes, perceived risk and safe sex intention among students of Politeknik Kuching Sarawak - Ho, Ai Chia (Universiti Malaysia Sarawak, (UNIMAS), 2010)
World Health Organization has ascertained that HIV/AIDS's pandemic is still one of the most important and urgent public health challenges facing mankind in the 21 S` century, with 60 percent of new infections are among young people between 15 to 24 years old. A cross sectional study, aimed to determine the prevalence of premarital sex and HIV-AIDS related knowledge, attitude, perceived risk and safe sex intention, was conducted among 270 students of Politeknik Kuching Sarawak, using a self-administered questionnaire. The prevalence of premarital sex among this target sample was 21.5 percent Higher prevalence of premarital sex was seen among male students, older students of more than 22 years old, students from Bidayuh ethnic group and those staying with friends or alone. These students had `moderate' level of knowledge on HIV/AIDS, attitude towards HIV/AIDS, perceived risk of having HIV/AIDS and safe sex intention. There were confounding influences of sociodemographic characteristics towards the level of knowledge on HIV/AIDS, perceived risk of having HIV/AIDS and safe sex intention. No significant difference was found between the mean score of attitudes towards HIV/AIDS with any socio-demographic variable. Lower prevalence of premarital sex was also associated with higher level of knowledge on HIV/AIDS, positive attitude towards HIV/AIDS and higher intention on safe sex practice. Any health promotion efforts for premarital sex abstinence for these young people should focus on improving these factors, i. e. knowledge, attitude, perceived risk and safe sex intention towards HIV/AIDS prevention.